Pengaruh Pengembangan Karir, Lingkungan Kerja, dan Motivasi terhadap Loyalitas Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Yogyakarta - Hadi, Syamsul; Purnamarini, Tri Ratna; Maharani, Fitri (Jurnal Maksipreneur, 2024)
The first inspection revealed several significant problems related to working conditions, according to the Yogyakarta City Investment and One-Stop Integrated Services Service. Employee comfort and productivity are negatively affected by inadequate lighting and poor air circulation in the workplace. Apart from that, limited facilities such as limited workspaces are also an inhibiting factor in improving employee abilities and skills, as well as opportunities to achieve desired career goals. Another problem was employee loyalty which needed to be increased, which was reflected in employee absenteeism during working hours. This research involved 60 employees as a population with sampling using the census method. Career advancement opportunities, a pleasant work environment, and intrinsic motivation together have a good and substantial influence on employee loyalty, according to research using multiple linear regression. Career development, work environment, and motivation simultaneously have a positive effect on employee loyalty. Employees tend to be more loyal to the company as a whole if these areas are improved.